Viral infections in hospitalized children in Germany during the COVID-19 pandemic: Association with non-pharmaceutical interventions - Terliesner, Nicolas; Unterwalder, Nadine; Edelmann, Anke; Corman, Victor; Knaust, Andreas; Rosenfeld, Leonard; Gratopp, Alexander; Ringe, Hannelore; Martin, Luise; von Bernuth, Horst; Mall, Marcus A.; Kallinich, Tilmann (Frontiers in Pediatrics, 2022)
Background: Non-pharmaceutical interventions (NPI) during the COVID-19 pandemic aimed at prevention of SARS-CoV-2 transmission also influenced transmission of viruses other than SARS-CoV-2. The aim of this study was to describe and compare the burden of common viral respiratory and gastrointestinal infections in children admitted to Berlin University Children´s Hospital (BCH) before and during the COVID-19 pandemic at different levels of public NPI measures. Methods: In this retrospective study, we analyzed the frequency of detection of common human respiratory and gastrointestinal viruses from January 2016 through January 2022 in all patients admitted to BCH. We compared virus detection before and during the COVID-19 pandemic at different levels of public NPI measures. Results: The frequency of detection of seasonal enveloped and non-enveloped viruses (Boca-, Corona-, Influenza-, Metapneumo-, Parainfluenza-, Rota-, and Respiratory Syncytial Viruses (RSV)) was diminished during the COVID-19 pandemic, whereas detection rates of non-seasonal viruses (Rhino-/Entero-, and Adenoviruses) were stable during the pandemic. After withdrawal of major NPI measures, we observed an out of season surge of the detection rates of Boca-, Corona-, Parainfluenzaviruses, and RSV. In contrast, no increased detection frequency was observed for Influenza-, Metapneumo-, and Rotaviruses as of January 2022. Conclusion: Corona-, Boca-, Parainfluenzaviruses, and RSV returned as frequently detected pathogens after withdrawal of major NPI measures. The out of season rise might be attributed to an “immune-debt” due to missing contact to viral antigens resulting in waning of population immunity during the COVID-19 pandemic.